THE EFFECT OF HIIT TRAINING ON SOME FUNCTIONAL INDICATORS AND STRAIGHT PUNCH SPEED ENDURANCE FOR YOUNG BOXERS WEIGHING 57-63 KG - Abd Ali Hamza, Dr. Haidar (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Boxing training is characterized by strength and speed, meaning a high ability to perform offensive and defensive movements. Boxing requires high physical preparation and scientifically codified training for the purpose of raising the physical capabilities of the boxers to complete the fight, more so towards the conclusion of the second and third rounds.This requires the efficiency of the circulatory and respiratory systems, and it also requires the safety and efficiency of the nervous system for what it needs. Boxing with high concentration while maintaining high energy levels throughout the fight. Therefore, the research study aimed to use high-intensity training for the purpose of developing the physical efficiency that a boxer needs, especially the maximum anaerobic capacity, because the dominant system is the anoxic system (lactic), as well as the enzymes that directly affect this system (LDH.CAT) and carry the speed of the straight punch of young boxers. The researcher used the experimental approach with two equal groups. The research sample was represented by young boxing players in the Iraq Club in Karbala Governorate, who numbered 10 boxers weighing 57-63 kg. High-intensity training (HIIT) was applied to the research sample at a rate of three number of sessions per week, 30 training sessions total. Through it, the training intensity was regulated to suit the nature of the method followed and the intensity of the fight. After that, post-tests were conducted for the research variables. The researcher used the statistical program SPSS to extract the research results, from which the researcher concluded that HIIT training had a significant impact on the variables investigated (maximum anoxic capacity, speed endurance). The straight punch and the LDH.CAT enzyme. In light of this, the researcher recommends the necessity of following training with intensity similar to the fight environment in order to adapt the boxers’ functional systems and to avoid a rapid decline in the boxers’ level during the fight.